APPLICATION OF EFFECTIVE COMBINATIONS IN TREATMENT OF RINOSINUSITIS - Безшапочний С. Б.; Сонник Н. Б.; Іванченко С. А. (World of Medicine and Biology, 2017)
The article describes the problem of treatment of patients with acute and chronic bacterial rhinosinusitis. To date, the benefits of combined medication are due to its ease of use and economic utility. For such drugs, a combination of decongestants hydrochloride with an antiseptic miramistin. An analysis of the results of treatment of patients with the use of this combination in adult concentrations was 0.1% / 0.01%, for children - 0.05% / 0.01%. Starting from 2 days in patients of the main group, the average value of severity of symptoms was less compared to the control. Patients in the main group noted better tolerability of the drug compared to the control group, the latter often had complaints of dryness of the mucous membrane. The number of hospital stay days decreased by 1.3 days in the main group compared to the control group. The obtained results testify to the effectiveness of the combination of hydrochloride with miramistin in the complex treatment of acute and chronic bacterial rhinosinusitis.